Pulsed magnetic field gradient on a tip for nanoscale imaging of spins - Leora Schein-Lubomirsky; Yarden Mazor; Rainer Stöhr; Andrej Denisenko; Amit Finkler (Communications Physics)
Abstract Nanoscale magnetic resonance imaging (nanoMRI) is crucial for advancing molecular-level structural analysis, yet existing techniques relying on permanent magnets face limitations in controllability and resolution. This study addresses the gap by introducing a switchable magnetic field gradient on a scanning tip, enabling localized, high-gradient magnetic fields at the nanoscale. Here, we demonstrate a device combining a metal microwire on a quartz tip with a nitrogen-vacancy (NV) center in diamond, achieving gradients up to 1 μT nm−1 at fields below 200 μT. This allows electron spin mapping with 1 nm resolution, overcoming challenges like emitter contrast and sample preparation rigidity. The current-controlled gradient, switchable in 600 ns, enhances precision and flexibility. Additionally, the metallic tip modifies Rabi power spatially, enabling selective spin manipulation with varying microwave effects. This innovation paves the way for advanced nanoMRI applications, including high-resolution imaging and targeted spin control in quantum sensing and molecular studies.